Kepribadian Narsistik pada Cerita Anak Kesombongan Jerapah Karya Ahmad Filyan - Ernawati , Tutik; Zahro , Alya Athifah Az; Kurniawan, Eva Dwi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study aims to determine the Narcissistic Personality found in the short story of giraffe vanity by Ahmad Filyan. The research method used is a qualitative descriptive method. The source of the data in this study is the short story of giraffe vanity by Ahmad Filyan. The data collection technique for the short story of giraffe vanity by Ahmad Filyan was carried out using documentary study techniques and descriptive analysis methods by reading the entire short story of giraffe vanity by Ahmad Filyan and rewriting the conversations contained in the short story. The object of this research focuses on the narcissistic personality contained in the short story of giraffe vanity by Ahmad Filyan, published by Serba Jaya Surabaya. The results of the study show that the arrogance (Narcissistic Personality) that occurs in short stories is that a person looks down on other people compared to himself for things he is not sure about and is overly confident that only he can get everything. In the Narcissistic Personality there is a feeling of title and respect, Shows arrogance, arrogant behavior or attitude.